2006
DOI: 10.1108/14777830610702502
|View full text |Cite
|
Sign up to set email alerts
|

Unsustainable development to sustainable development: a conceptual model

Abstract: Purpose -Modelling of sustainable development is essential, as environmental protection is regarded as a top global priority in the twenty-first century. The basic objective of this paper is to provide a conceptual framework, named the Four Forces model for diagnosing the process of sustainable development. Design/methodology/approach -Michael Porter's Five Forces model serves as a starting-point to derive the Four Forces model. The Four Forces model, which is developed based on Back Casting technique, shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Ecolabelling can help marketers differentiate their offerings in the mind of the consumer and have a positive effect on consumers' decision making regarding the purchase of the product, thereby increasing the sale of the company's offerings (Bougherara and Piguet, 2009). It has been found that environmentally conscious customers prefer ecolabelled products (Mohan Das Gandhi et al, 2006). Previous studies suggest that an ecolabel motivates the consumer to purchase green products (Harris, 2007;Rahbar and Wahid, 2011;Young et al, 2010).…”
mentioning
confidence: 99%
“…Ecolabelling can help marketers differentiate their offerings in the mind of the consumer and have a positive effect on consumers' decision making regarding the purchase of the product, thereby increasing the sale of the company's offerings (Bougherara and Piguet, 2009). It has been found that environmentally conscious customers prefer ecolabelled products (Mohan Das Gandhi et al, 2006). Previous studies suggest that an ecolabel motivates the consumer to purchase green products (Harris, 2007;Rahbar and Wahid, 2011;Young et al, 2010).…”
mentioning
confidence: 99%
“…Recycling is an essential practice in a society that demands environmental conservation; however, it was observed here that recycling is not valued by the population, with the findings of this study showing that 1.7% of consumers practice recycling. Some studies show that factors such as education level and age have no relevance in determining recycling practice [9], showing these factors do not exhibit significant differences with respect to recycling practices [24]. Unlike the findings of Kelly et al [32], who found that age had a significant relationship with recycling behavior, young people tend to be indifferent (sometimes recycle), and middle-aged groups tend to recycle more frequently.…”
Section: Discussionmentioning
confidence: 95%
“…Reduction practices have significant value in this regard [8,9] because a reduction in the consumption of products directly decreases the amount of waste that goes to the final disposal sites [7,9], extending the useful life of the landfill. However, this practice is difficult to promote because its realization usually requires a major adjustment in lifestyle [10]; hence, the minimization of solid waste has received less attention than recycling practices [11].…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, as consequências negativas da enorme geração de resíduos industriais sobre o meio ambiente e os recursos naturais não podem ser ignoradas (MOHAN DAS GANDHI et al, 2006;MALLAK et al, 2016).…”
Section: Resíduos Sólidos Industriaisunclassified